Marketing Analysis Of Cayenne Pepper In Paya Benua Village, West Mendo District, Bangka Regency - Venny Oktari; Rostiar Sitorus; Rufti Puji Astuti (Universitas Muhammadiyah Palembang, 2024)
The research will be conducted in June 2023 in Paya Benua Village, West Mendo District, Bangka Regency. The purpose of this study is to analyze marketing channels, understand the marketing functions carried out by marketing agencies, calculate marketing profits, analyze marketing efficiency by calculating marketing margins, determine farmer's share value, and measure cayenne pepper marketing efficiency in Payacontinent Village, West Mendo District, Bangka Regency. The research method used is a survey method with probability sampling techniques, where 30 farmers are randomly selected as samples. The sample of traders was determined using the Snowball Sampling method, with the results of 6 middlemen and 9 retailers. The results showed that the marketing function performed by farmers and traders involves buying, selling, transporting, sorting & grading, risk bearing, and market information. The marketing of cayenne pepper in Payacontinent Village uses three marketing channels: Channel I (Farmers-Middlemen-Consumers), Channel II (Farmers-Retailers-Consumers), and Channel III (Farmers-Middlemen-Traders-Retailers-Consumers). Marketing profits obtained from Channel I amounted to Rp2,517/kg, Channel II amounted to Rp7,632/kg, and Channel III amounted to Rp8,572/kg. Marketing efficiency on all channels is classified as efficient, with values of 13.61%, 8.95%, and 13.82%, respectively. Of the three channels, Channel II is considered the most efficient.